2010
DOI: 10.1001/archsurg.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Blood Transfusion During Emergency Trauma Operations

Abstract: Intraoperative CS provides an effective and cost-efficient resuscitation strategy as an alternative to allogeneic blood transfusion in trauma patients undergoing emergency operative procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…Another barrier to the use of such a procedure would be a worsening of coagulopathy in a patient with active bleeding. According to Brown et al 21 , their studies suggested the opposite, stating that patients in the control group received more units of plasma than reinfused ones. The same can be observed in a the work of Bowley et al 26 , in which there were no significant differences between the groups analyzed.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Another barrier to the use of such a procedure would be a worsening of coagulopathy in a patient with active bleeding. According to Brown et al 21 , their studies suggested the opposite, stating that patients in the control group received more units of plasma than reinfused ones. The same can be observed in a the work of Bowley et al 26 , in which there were no significant differences between the groups analyzed.…”
mentioning
confidence: 99%
“…The total cost of autotransfusion was US$ 63,252.00. If the same amount of blood were to transfused with blood products, the cost would be around US$ 114,523.00, a saving of around 45% 20,21 . A study by Brown et al 21 in 2010 showed that autotransfusion had a cost of US$ 1,616 per patient.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2010, reporting on a study from a level 1 trauma centre in the USA, Brown and colleagues described 47 patients undergoing surgery after injury who received IBS and autologous blood transfusion 10. Patients were compared with 47 similar patients who underwent similar surgeries (mostly laparotomies) and required transfusion, but who did not receive cell salvage as part of their resuscitation.…”
mentioning
confidence: 99%